Caracterização in vitro de uma resina composta bulk fill contendo partículas pré-reagidas de ionômero de vidro (S-PRG) - Clóvis Ciryllo Limonge Neto (2019)
In the oral environment, composite resin restorations are subject to physical actions, from occlusal wear and tear, and chemical actions, through contact with saliva and food. The effects of these physicochemical processes are directly related to the composition characteristic of resin restorative material. Laboratory assays are especially important for assessing the physical strength and chemical stability of restorative materials. The objective of the study was to perform in vitro characterization of a bulk fill composite containing glass ionomer pre-reacted particles (S-PRG) (Beautifil-Bulk, Shofu Inc). The dependent variables were flexural strength (FS), water sorption (WS) and solubility (SL), degree of conversion (DC), elution of monomers in distilled water and surface morphology in scanning electron microscopy (SEM). The independent variables were the shades of the composite resin, in five levels, and the storage time of the specimens, in six levels. The FS, WS and SL assays were performed according to the methodology recommended by ISO 4049:2009. For monomer elution assay and surface analysis in SEM specimens were made with 15 mm diameter and 1 mm thickness, using A3 shade resin. The degree of conversion was determined in cylindrical specimens measuring 1 x 1 mm with A3 shade resin. For the preparation of all the specimens, the Radii-Cal LED light curing unit (SDI Inc., Victoria, Australia, 1200 mW / cm2) was used. After the incubation periods of the samples in distilled water (10 min, 24 h, 7 days, 30 days, 3 and 6 months), analyzes were performed in high performance liquid chromatography (HPLC) for the identification and quantification of elution monomers using Bis-GMA and TEGDMA standards. For surface analysis, specimens incubated in distilled water (7 days, 30 days, 3 and 6 months) were sprayed with 4 nm of carbon and were evaluated in SEM (FEI-Quanta 200, FEG). The results were expressed as mean and standard deviation. Normality tests (Kolmogorov-Smirnov and Shapiro-Wilk) and homoscedasticity test (Levene) were performed. Analysis of Variance (ANOVA) and multiple comparison test, and Kruskal-Wallis test verified the differences between the levels of the factors under study. The significance level of 5% was set. There was no significant difference among the resin shades for FS, WS and SL (p> 0.05). The mean (SD) of DC was 59.37 (14.49)%. TEGDMA was identified at all time points with the highest concentrations at 30 days and 3 months of storage. Bis-GMA was not detected in any of the solutions. SEM images showed morphological changes suggestive of surface roughness at 6 months of storage. The composite resin Giomer Beautifil-Bulk reached the requirements of ISO 4049:2009 for FS, WS and SL and presented acceptable DC. There was no release of Bis-GMA and TEGDMA was detected throughout the 6-month evaluation period.